Ion-Plasma Formation of Nanosized Coatings with Fractal Topology - Potapov, Alexander; Tupik, Viktor; Margolin, Vladimir; Kostrin, Dmitrii (International Journal of Integrated Engineering, 2024)
Nanosized coatings with fractal topology have significant technological applicability due to their unique properties. There are several ways to provide fractalization of the coating, one of which is placing a seed into the vacuum chamber. The most used method for producing nanosized coatings is magnetron sputtering, which allows obtaining a high-quality film with a sufficiently high productivity. The notable disadvantage of such devices is a low degree of ionization of the plasma flux, which leads to poor adhesion of the obtained coating. More promising is the electric arc spraying of matter from the plasma by an anomalous glow discharge, which in turn has a significant concentration of the droplet fraction existing together with the plasma flux. These droplets greatly increase the coating roughness and make electric arc installations inapplicable in nanotechnology. A specially designed arc evaporator, including metallic nonmagnetic dampers, provides elimination of the droplet fraction. Experiments on the deposition of titanium nitride and copper coatings on high-carbon steel substrates have shown both the possibility of obtaining uniform nanostructured coatings and coatings with fractal topology in the case of introducing specially prepared seed into a vacuum chamber.